The Effect Of Teacher Teaching Motivation On Student Learning Achievement In Islamic Religious Education (PAI) At State High School 1 Baso Bukittinggi - Charles; Yusutria; Yuherman; Hanif Cahyo Adi Kistoro (JOSSE: Journal of Social Science and Economics, 2022)
Learning is a process in which teachers and students interact in educational situations to achieve specific goals. Its intended purpose is to teach. One of the pedagogical goals achieved is the level of student achievement. With the high achievement, students have a good expression of knowledge. Motivation is one of the factors that influence student success. Learning motivation requires increasing school academic efforts. This study examined the effect of learning motivation on student achievement in Islamic Religious Education (PAI) subjects. The type of research used is quantitative research. The population of this study consisted of 90 students of SMA Negeri 1 Baso Bukittinggi, with a sample of 29 students. Data was collected through a questionnaire—data analysis using simple regression analysis with the help of the SPSS version 23 program . Based on the test results, the correlation value (r) is 0.852. This means that variable X (teaching motivation of teachers) with variable Y (Student Learning Outcomes) has a robust correlation because the correlation value is between 0.80 and 1.00 . These results conclude that the higher the student's learning motivation, the higher the learning achievement